The Impact of Metal Nanoparticles on the Immunoregulatory and Therapeutic Properties of Mesenchymal Stem Cells - Holan, Vladimir; Cervena, Tereza; Zajicova, Alena; Hermankova, Barbora; Echalar, Barbora; Palacka, Katerina; Rossner, Pavel; Javorkova, Eliska (Stem cell reviews and reports, 2023)
Negative impacts of nanomaterials on stem cells and cells of the immune system are one of the main causes of an impaired or slowed tissue healing. Therefore, we tested effects of four selected types of metal nanoparticles (NPs): zinc oxide (ZnO), copper oxide (CuO), silver (Ag), and titanium dioxide (TiO2) on the metabolic activity and secretory potential of mouse mesenchymal stem cells (MSCs), and on the ability of MSCs to stimulate production of cytokines and growth factors by macrophages. Individual types of nanoparticles differed in the ability to inhibit metabolic activity, and significantly decreased the production of cytokines and growth factors (interleukin-6, vascular endothelial growth factor, hepatocyte growth factor, insulin-like growth factor-1) by MSCs, with the strongest inhibitory effect of CuO NPs and the least effect of TiO2 NPs. The recent studies indicate that immunomodulatory and therapeutic effects of transplanted MSCs are mediated by macrophages engulfing apoptotic MSCs. We co-cultivated macrophages with heat-inactivated MSCs which were untreated or were preincubated with the highest nontoxic concentrations of metal NPs, and the secretory activity of macrophages was determined. Macrophages cultivated in the presence of both untreated MSCs or MSCs preincubated with NPs produced significantly enhanced and comparable levels of various cytokines and growth factors. These results suggest that metal nanoparticles inhibit therapeutic properties of MSCs by a direct negative effect on their secretory activity, but MSCs cultivated in the presence of metal NPs have preserved the ability to stimulate cytokine and growth factor production by macrophages.
Keywords: vaskulární endoteliální růstový faktor A; Animals; cytokiny; kovové nanočástice; Mesenchymal Stem Cells; zvířata; mezenchymální kmenové buňky; Mice; Cytokines; Vascular Endothelial Growth Factor A; Metal Nanoparticles; myši